Designing double skin facade venting regimes for smoke management. (15th March 2018) - Thomas, Geoff; Al‐Janabi, Mohammad; Donn, Michael
Summary: The impact of sustainable building features on fire safety can be positive, neutral, or negative. An expert group ranked double skin facades (DSF) as being high risk due to a lack of knowledge of strategies to prevent fire and smoke spread through a DSF. Computational fluid dynamics modelling of prototype buildings with a 0.5 and 1.0‐m‐wide DSF has been carried out. External and internal vents to the DSF have varied in size and location, as well as the fire location, whether the building is fitted with sprinklers and other variables. The sensitivity of the model to grid resolution was checked using the 2 extremes of ventilation. Provided the vents to the DSF close in a fire, and flashover does not occur in rooms adjoining the DSF, or sprinklers are installed, smoke spread to higher floors via the DSF is limited. If a building is designed so the vents to the exterior from the DSF are greater in effective area than those from the interior to the DSF smoke flow will be predominantly to the outside of the building, and fire engineering design is likely to show that occupants will have time to escape.